Structural aberrations affecting the MYC locus indicate a poor prognosis independent of clinical risk factors in diffuse large B-cell lymphomas treated within randomized trials of the German High-Grade Non-Hodgkin's Lymphoma Study Group (DSHNHL). - Klapper, W.; Stoecklein, H.; Zeynalova, S.; Ott, G.; Kosari, F.; Rosenwald, A.; Loeffler, M.; Trumper, L.; Pfreundschuh, M.; Siebert, R. (Leukemia, 2008)
Recent retrospective studies of heterogeneously treated patients have suggested that chromosomal aberrations of the MYC gene locus indicate an unfavorable prognosis in diffuse large B-cell lymphoma (DLBCL). Here, we investigated the prognostic impact of MYC aberrations analyzed by interphase fluorescence in situ hybridization in 177 patients with de novo DLBCL treated within the two prospective, randomized trials non-Hodgkin's lymphoma NHL-B1 and NHL-B2. MYC aberrations were detected in 14 DLBCL (7.9%). In a univariate analysis compared with MYC-negative DLBCL, MYC-positive cases showed a significantly shorter overall survival (OS) (P=0.047) and relevantly, though not significantly, shorter event-free survival (EFS) (P=0.062). In a Cox model adjusted for the international prognostic index, the presence of a MYC gene rearrangement was the strongest statistically independent predictor of OS (relative risk 3.4, P=0.004) and EFS (relative risk 2.5, P=0.015), and this also held true when the cell-of-origin signature detected by immunohistochemistry was included in the model.
Keywords: Adult; Aged; *Chromosome Aberrations; Disease-Free Survival; Female; *Gene Expression Regulation, Neoplastic; Genes, myc/*genetics; Germany/epidemiology; Humans; Immunohistochemistry; Kaplan-Meier Estimate; *Lymphoma, Large B-Cell, Diffuse/genetics/mortality/therapy; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Randomized Controlled Trials as Topic; Retrospective Studies; Risk Factors; Young Adult